NILAI PENDIDIKAN KARAKTER DALAM NOVEL NGERI NGERI SEDAP KARYA BENE DIONYSIUS RAJAGUKGUK - Sirait, Antonius; Gafar, Abdoel; Sumiharti, Sumiharti (Universitas Batanghari, 2024)
This research was motivated by the researcher's desire to analyze the representation of aspects of absurdity in drama texts. This research aims to describe the value of character education from the aspects of honesty, discipline, hard work, creativity, independence and responsibility in the context of character education in the novel Ngeri Ngeri Sedap by Bene Dionysius Rajagukguk. This research uses a qualitative descriptive research type. Qualitative descriptive research is research intended to investigate circumstances, conditions or other matters, the results of which are presented in the form of a research report in the form of data. The data in this research are in the form of quotations from the novel NGERI NGERI SEDAP by Bene Dionysius Rajagukguk with aspects of absurdity which include; honest, disciplined, hard working, creative, independent and responsible. The results of this research illustrate that there are aspects of character education values in the novel NGERI NGERI SEDAP in the aspects of honesty, discipline, hard work, creativity, independence and responsibility. From these six aspects. The most dominant aspect found was the honest aspect, while the least found aspect was the hard work aspect. Keywords: values, education, characters, novels